Multilocus Genotyping of Pneumocystis jirovecii from Deceased Cuban AIDS Patients Using Formalin-Fixed and Paraffin-Embedded Tissues - Vicente Friaza; Yaxsier de Armas; Virginia Capó; Rubén Morilla; Arturo Plascencia-Hernández; Héctor R. Pérez-Gómez; Enrique Iglesias; Luis Fonte; Carmen de la Horra; Enrique J. Calderón (Journal of Fungi, 2021)
The results of the genotypic characterization of Pneumocystis jirovecii are described in lung tissue samples from 41 Cubans who died of AIDS with pneumocystosis between 1995 and 2008. Histological sections of the lung preserved as formalin-fixed and paraffin-embedded tissue were examined. PCR amplification and nucleotide sequencing of the two mitochondrial genes (large and small) of the pathogen allowed verification of a predominance of genotype 3 (85T/248C) of the large mitochondrial gene and genotype 3 (160A/196T) of the small mitochondrial gene over a period of 14 years (1995–2008). These results suggest that the 85T/248C//160A/196T genotype circulates with the highest frequency (81.3%) among AIDS patients in Cuba. Multilocus analysis indicates a limited circulation of pathogen genotypes on the island with the existence of a clonal genotype with an epidemic structure. Furthermore, it appears that circulating strains of P. jirovecii have not developed mutations related to sulfonamide resistance. Taken together, the data in this study revealed important elements about pneumocystosis in Cuban patients dying of AIDS and the usefulness of formalin-fixed and paraffin-embedded samples to carry out molecular epidemiology studies of P. jirovecii.